Sociocultural adaptation of Chinese international students in the United States and its influencing factors - Wei, Xiaofang (Frontiers in Psychology, 2025)
As the number of international Chinese students studying in the US continues to rise and cross-cultural adaptation stress and difficulties they experience may hinder their adaptation culturally, socially, emotionally and academically, understanding their sociocultural adaptation challenges in the host culture becomes increasingly important. The research investigated the cross-cultural adjustment of Chinese students in the US, focusing on the sociocultural adaptation aspect and its influencing factors. A convenience sample of 199 Mainland Chinese students from Kentucky University completed questionnaires assessing sociocultural difficulties (using Sociocultural Adjustment Scale) and psychological well-being (measured by Satisfaction with Life Scale). Factor analysis revealed that sociocultural adaption could be categorized into three sub-scales: interpersonal adaptation, environmental adaptation and cultural adaptation. Among key demographic variables (duration in the US, educational level, and language proficiency) and situational variables (psychological adaptation and social support from host nationals), the multiple regression analyses revealed social support exerts the greatest influence on sociocultural adaptation, while education level has the negative impact on sociocultural adaptation. Language proficiency and social support from host nationals are the strong positive predictors of interpersonal adaptation. Length of residence and psychological adaptation drive environmental adaptation and cultural adaptation most. Limitations of this study, along with possible explanations for the findings, were also discussed.